Peptide Antigen Concentration Modulates Digital NFAT1 Activation in Primary Mouse Naive CD8(+) T Cells as Measured by Flow Cytometry of Isolated Cell Nuclei - Gallagher, Michael P. (Immunohorizons, 2018)
Circulating naive T cells exist in a quiescent state. After TCR contact with the cognate peptide presented by APCs in secondary lymphoid structures, T cells undergo a period of rapid transcriptional changes that set the stage for fate-determining effector or memory programming. We describe a novel method to analyze TCR signaling pathway activation in nuclei isolated from primary mouse naive T cells after stimulation with natural peptide Ags. We prelabeled cells with cell tracking dye to easily distinguish CD8(+) T cell nuclei from APC nuclei by conventional flow cytometry. Using this approach, we observed clear digital activation of NFAT1 transcription factor in OT-I T cells stimulated with OVA peptide presented by bulk splenocytes. OVA concentration had discrete control over the fraction of the cells that translocated NFAT1, indicating that a distinct threshold amount of TCR signaling is required to switch on NFAT1 in naive T cells. This behavior was cell contact dependent and qualitatively more exact than the NFAT1 response in ionomycin-stimulated naive T cells. These data contribute to our understanding of the digital behavior of TCR signaling components documented in other studies and indicate how T cells might discriminate log-fold changes in Ag availability during an actual infection. Overall, these results highlight the potential of this coculture nuclei isolation protocol to address stimulation-dependent translocation of proteins in primary lymphocytes.